(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. Exercise-induced proteinuria is predominantly caused by alterations in renal hemodynamics. The present study was conducted to determine the effect of aerobic exercise in hypoxia on proteinuria and hematuria. Materials and Methods. The study population consisted of 17 physically trained healthy young men. They were asked to attend in 4 sets of 30-minute running sessions, separated by 72-hour resting intervals, to attain 70% of maximal heart rate in normoxia (fraction of inspired oxygen of 0.21) and 3 different levels of hypoxia (lower fraction of inspired oxygen equivalent to the heights of 2750 m, 3250 m, and 3750 m above the sea level). Urine samples were collected before exercise and immediately and 1 hour after each session to measure total protein, albumin, beta2-microglobulin, and erythrocyte count. Results. Postexercise urinary total protein, albumin, and beta2-microglobulin showed significant increases compared to basline values, while no significant difference was found in urinary total protein between hypoxia and normoxia conditions. However, there was a significant positive correlation between the amount of albuminuria and the height (P = .01), and a significant difference in beta2-microglobulinuria between normoxia and the simulated 2750-m altitude (P = .007), which disappeared at higher elevations. None of the participants developed hematuria. Conclusions. Aerobic exercise with moderate intensity in trained men might induce mixed proteinuria with glomerular predominance correlated with height, while tubular component loses this relation at altitudes above 2750 m. Further research on the influence of exercise on urinary abnormalities, particularly in different environmental conditions, is recommended.